Preliminary characterization of a bacteriocin-like substance produced by a Bacillus subtilis isolated from Argentinean vegetable food - Fangio, Maria Florencia (2013)
Bacillus spp. produces a large number of antimicrobial peptides and includes a variety of species of industrial importance. The aim of this study was to characterize the antimicrobial activity associated with a Bacillus subtilis strain. The activity of the crude bacteriocin-like substance (CBLS) was dependent on the components of the culture media and was detected in the exponential phase of growth. The CBLS was stable at a variable pH range and at 100°C, but it was inactivated by sterilization conditions. It was also stable to storage at refrigeration and freezing temperatures for a considerable time. The mode of action of the antimicrobial activity was bacteriostatic and the effect on the cell membrane was determinated by Fourier transform infrared (FTIR) spectroscopy.